Transformer-less Voltage Stabilizer Controlled By ProportionalPlus-Integral (PI) Controlle - Candidus U Eya; Emenike C Ejiogu; Marcel U Agu; Damian B Nnadi (Journal of Power Electronics and Devices, 2019)
Transformer-based voltage stabilizers are characterized by large size, heavy weight, noise pollution, expensive production, unreliable operation and have limited ability to stabilize output voltage. To overcome this problem, a pulse-width modulated transformerless voltage stabilizer is considered in this paper. The output voltage variation is stabilized by Plus Integral (PI) controller. The main properties of this proposed system are: (i) It is light in weight and occupies small space; (ii) It has low total harmonic distortions; (iii) the output possesses pure sine wave signals; (iv) It is very cheap for mass production. In this paper, we applied the modulation index of 0.86 in the proposed system (PS). The total harmonic distortion, THD of 3.968% was realized and we ensured constant voltage output of proposed system within the input voltage band of (120-230) VAC. The proposed topic can be applied at homes, offices and also in industries.